Driving Performance and User's Evaluation of Self-Balancing Personal Mobility Vehicle with a Pedal Driving Mechanism. (8th July 2015) - Jeong, Seonghee; Takahara, Satoshi; Takahashi, Takayuki; Hiroi, Yutaka; Matsumoto, Osamu
In this paper, we propose a self-balancing personal mobility vehicle with a hybrid driving mechanism, called as Wi-PMP, and discuss its features from the perspectives of its power-assist driving performance and a rider's evaluation. The mobility vehicle consists of a wheeled inverted pendulum type mobile platform, and a hybrid driving mechanism that can use human and motor power together for driving. By performing a bump driving, a slope driving, and a outdoor driving experiment, we confirm that the proposed hybrid mechanism is valid for the integration of human and motor power, and is effective to increase the driving power and reduce electrical load on motors and batteries. We conducted several experiments to investigate the rider's evaluation on a sit-riding method compared to a stand-riding one. The questionnaire results showed that a rider felt more comfortable in the case of the sit-riding method when getting on and off, and when driving the mobility vehicle. This implies that riding-type self-balancing vehicles such as Wi-PMP have the potential to become familiar personal mobility vehicles in daily life.